B. R. Ambedkar on the Practice of Public Conscience: A Critical Reappraisal. (January 2023) - Yadav, Vivek Kumar; Dasgupta, Shomik; Kumar, Bharath
This article discusses the importance of 'public conscience' in B. R. Ambedkar's political thought. Ambedkar consistently defended public conscience as a democratic value in his writings and speeches. Public conscience referred to collective responsibility, social justice and the public deliberation of what constitutes the social good. Ambedkar consistently expressed the unequivocal belief that public conscience would bring about a moral transformation in Indian society through a collective ethical stance against all forms of social oppression. He conceptualized public conscience as a method by which a democratic and ethical Indian society could come about and flourish. This article interrogates his ideas concerning public conscience through a detailed reading of his works, focusing particularly on his 1943 speech, Ranade, Gandhi and Jinnah .